Examining the seagrass-associated fauna and utilization of the mixed seafrass beds in Brgy. Tando, Nueva Valencia, Guimaras - Gange, Jan Elysia Huelar (2017.)
The seagrass-associated macrofaunal assemblages and its utilization by the local community were assessed in Barangay Tando, Nueva Valencia, Guimaras. Barangay Tando is a coastal barangay with a wide distribution of seagrass beds around its coasts. Fishing is the main source of livelihood where longlines and gill nets were commonly employed. Seagrass-associated macrofauna were assessed in three stations using the transect-quadrat method. Sea urchins (Tripneustes gratilla and Diadema sp.), sea stars (Protoreaster nodosus), and wide variety of sea shells were commonly found in the area. Interviews with key informants and from local respondents revealed that the seagrass beds play an important role as a gleaming area for edible seashells and invertebrates such as sea hares and sea cucumbers. Spear fishing and gill net fishing are also done in the vicinity of the seagrass beds. The seagrass beds act as an alternative fishing area especially during harsh weather conditions. Catches of fishers from Brgy. Tando are transported and sold to other markets in Guimaras, highlighting the importance of the area as a source of fish. These results of this study show that seagrass beds in the vicinity of Brgy. Tando provides vital economic and ecological services to the local community and other areas in Guimaras.
Thesis (Bachelor Science in Fisheries) Institute of Fisheries Policy and Development Studies, College of Fisheries and Ocean Sciences, University of the Philippines Visayas
Keywords: Seagrass; Fauna; Seagrass beds; Brgy. Tando, Nueva Valencia, Guimaras